Relative paleointensity (RPI) and age control in Quaternary sediment drifts off the Antarctic Peninsula. (1st May 2019) - Channell, J.E.T.; Xuan, C.; Hodell, D.A.; Crowhurst, S.J.; Larter, R.D.
Abstract: Lack of foraminiferal carbonate in marine sediments deposited at high latitudes results in traditional oxygen isotope stratigraphy not playing a central role in Quaternary age control for a large portion of the globe. This limitation has affected the interpretation of Quaternary sediment drifts off the Antarctic Peninsula in a region critical for documenting past instability of the West Antarctic Ice Sheet (WAIS) and Antarctic Peninsula Ice Sheet (APIS). Here we use piston cores recovered from these sediment drifts in 2015 during cruise JR298 of the RRS James Clark Ross to test the usefulness for age control of relative paleointensity (RPI) data augmented by scant δ 18 O data. Thermomagnetic and magnetic hysteresis data, as well as isothermal remanent magnetization (IRM) acquisition curves, indicate the presence of prevalent magnetite and subordinate oxidized magnetite ("maghemite") in the cored sediments. The magnetite is likely detrital. Maghemite is an authigenic mineral, associated with surface oxidation of magnetite grains, which occurs preferentially in the oxic zone of the uppermost sediments, and buried oxic zones deposited during prior interglacial climate stages. Low concentrations of labile organic matter apparently led to arrested pore-water sulfate reduction explaining oxic zone burial and downcore survival of the reactive maghemite coatings. At some sites, maghemitization has a debilitating effect on RPI proxies whereas at other sites maghemite is less evident and RPI proxies can be adequately matched to the RPI reference template. Published RPI data at ODP Site 1101, located on Drift 4, can be adequately correlated to contemporary RPI templates, probably as a result of disappearance (dissolution) of maghemite at sediment depths >∼10 m. Highlights: Sedimentary relative paleointensity in late Quaternary age control off Antarctica. Buried and surficial oxic zones contain oxidized magnetite (maghemite) Authigenic maghemite limits the use of relative paleointensity proxies Rare planktic forminifera yield discontinuous oxygen isotope data Relative paleointensity and scant δ 18 O provide chronological constraints